2020
DOI: 10.9734/cjast/2020/v39i830596
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Low Cost Drip Filter

Abstract: Irrigation water is many a time contaminated with physical, chemical and biological impurities. Proper filtration is of paramount importance to prevent clogging in drip irrigation system thereby aiding in reduced maintenance of the micro irrigation system. This study was conducted on Development and Evaluation of Low cost filters in the Network project on “Engineering Interventions in Micro Irrigation Systems (MIS) for improving water productivity” under Consortia Research Platform on Farm Mechanization and Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
1
1
0
Order By: Relevance
“…Where this media included two layers each contains a large amount of sand which resulted in more effective filtration with this treatment. This result confirmed with (Kannan et al, 2020).…”
Section: Removal Efficiencysupporting
confidence: 86%
“…Where this media included two layers each contains a large amount of sand which resulted in more effective filtration with this treatment. This result confirmed with (Kannan et al, 2020).…”
Section: Removal Efficiencysupporting
confidence: 86%
“…Chi et al (2021) and Mesquita, Testezlaf and Ramirez (2012) pointed out that the drop in pressure is signifi cantly aff ected by the speed of fi ltration. Kannan et al (2020) reported that as the fl ow rate increases, the retained particles and the effi ciency of the fi lter increase, intensifying the drop in pressure and resulting in a greater need for cleaning. If the need for cleaning is high, it is essential to install an automatic backwashing system in order to improve the practicality of the fi ltration system (KHAN; REHMAN;JAMAL, 2017;RIBEIRO et al, 2005).…”
Section: Cleaning Prediction and Backwashingmentioning
confidence: 99%